Culture of Argumentative Discourse Formation as an Inevitable Element of Professional Development of Journalists - Sultanbayeva, G S; Golovchun, A A (Farabi Journal of Social Sciences, 2016)
Modern period of educational development is characterized by various attempts in higher quality and effective result provision. Having acquired the modernized educational paradigm, our academic community placed the personality development through language and culture under the focus of primary research. The competency-based concept claims for professionally ready specialists who are capable to solve practical problems. In this sense, and under the circumstances of current development of Kazakhstani society, it is inevitable to form the ability to conduct argumentative discourse as the crucial element of intercultural communicative competence. This article particularly states the necessity of culture of argumentative discourse formation presents theoretical background of its organization and aims at identifying important argumentative skills within educational process.